The Effect of a Combination of Group Therapy and Support on the Self-Efficacy and Deviant Behavior of Adolescents - Winda Kusumawardani; Nursalam Nursalam; Hanik Endang Nihayati (Universitas Airlangga, 2020)
Introduction: The purpose of this study was to investigate the effect of combination therapy and supportive group therapy on the self-efficacy and deviant behavior among adolescents.Methods: The design of this study was quasi-experimental (pre-post test with a control group design). The population was based on the inclusion criteria of young men aged 15-19 years old in high school in Surabaya and the exclusion criteria was adolescents with physical disabilities, mental disorders and illness. A sample of 62 respondents (31/31) was collected using purposive sampling. The independent variable was a combination of group therapy and supportive therapy. The dependent variable was self-efficacy and deviant behavior. The intervention was given 4 times over 4 weeks and the control group was given a standard intervention. The data was collected using a self-efficacy questionnaire. The analysis was conducted using MANOVA.Results: In the intervention and control groups, there was a significant difference between self efficacy and deviant behavior in the adolescents before and after the intervention with a value of 0,000 (p <0.05).Conclusion: The increase in self-efficacy in the intervention group can be seen from the magnitude of the sub-variables. The deviant behavior variable decreased. The increase in the self-efficacy intervention group was due to the presence of facilities that helped the students to find information and explore their potential. The decrease in the deviant behavior variables is due to their increased knowledge and the positive support from their peer groups.